The Supply‐Side Determinants of Loan Contract Strictness - MURFIN, JUSTIN (Journal of Finance, 2012)
ABSTRACT Using a measure of contract strictness based on the probability of a covenant violation, I investigate how lender‐specific shocks impact the strictness of the loan contract that a borrower receives. Banks write tighter contracts than their peers after suffering payment defaults to their own loan portfolios, even when defaulting borrowers are in different industries and geographic regions from the current borrower. The effects persist after controlling for bank capitalization, although bank equity compression is also associated with tighter contracts. The evidence suggests that recent defaults inform the lender's perception of its own screening ability, thereby impacting its contracting behavior.